Analysis of employee attitudes and perceptions towards cancer survivors: A literature review - Mamesah, Adriana; Winarto, Eko; Yunani, Yunani (Institute of Computer Science (IOCS), 2024)
Cancer survivors face significant challenges in reintegrating into the workforce, often impacted by biased attitudes and perceptions from colleagues and employers. These biases can hinder their productivity and professional satisfaction, emphasizing the need for more inclusive and supportive workplace environments. This descriptive literature review aims to summarize and synthesize existing research on employee attitudes and perceptions among cancer survivors. Utilizing a a inclusion and exclision criteria, the study identifies, screens, and includes relevant papers from various databases, focusing on articles published between 2010 and 2024. The findings the study found the complex relationship between employment, public perceptions, and support systems for cancer survivors re-entering the workforce. A collaborative approach involving healthcare providers, employers, and the public is crucial for optimizing the return-to-work experience.